Pemerintahan Provinsi Lampung 1945-1964 - Arizka Waranegara (Fiat Justisia: Jurnal Ilmu Hukum, 2013)
This is a library research about political elite contestation in Lampung from 1945 until 1964, at that time there are three major ideology, first is Islam, second is Nationalism and third is Communism. In the old orde era, the elite politics competition in the national level describe the same thing with the local level. If in the national level there are three major ideology, in Lampung also three ideology had played important role, the Party Communist (PKI), Indonesian Nationalsit Party (PNI) and Masyumi (Islamic Faction). In the first political stage after Independence of Indonesia. In 1964, there was a first Lampung’s Governor Election, at that time R.A Zulkifli Warganegara had appointed to be Lampung first Governor, but because of the political intervention his position was replaced by Koesno Danopoyo which was fully supported by Communist Party. This is a decsriptive qualitative research, the main data comes from indepth interview and documentation. The results shown that there is basic difference between Lampung’s political elite contestation in the old orde era and reformation era. In the old orde era the competition based on ideology but in the reformation era the competition based on purely political interest.Keywords: contestation, political elite and election